401 Ventilation Parameters during Resuscitation: Comparison of two Different Devices in a Mannequin Model with and without Distraction. (October 2012) - Gupta, N; Thio, M; Dawson, JA; Kamlin, COF; Schmoelzer, GM; Davis, PG
Abstract : Background and Aims: Positive pressure ventilation is a common intervention in neonatal resuscitation. Distraction, type of device and experience may influence performance. Studies have not included self-inflating bags (SIB) equipped with a PIP manometer and expiratory PEEP valve. We aimed to compare clinicians' ability to ventilate a mannequin using a SIB with additional manometers against a T-piece (TP), with and without distraction. Method: 50 medical and nursing staff were tested using standarised case scenarios with a leak free intubated mannequin. Participants targeted PIP 30 cmH2 O, PEEP 5 cmH2 O, inflation rate (IR) 60 inflations/minute with both devices in randomised order. We analysed PIP, PEEP, IR, expired tidal volume (TVe), professional group and compared devices during baseline and 3 minutes of distraction. Results: 12, 981 inflations were analysed. Mean (SD) ventilation parameters are shown in table . When analysed by operator, more variation was observed in IR (P=0.029) and TVe (P=0.002) with SIB during distraction. Conclusions: Clinicians' general performance when using a SIB where PIP and PEEP are displayed is comparable to a T-Piece, however more variation in IR and TVe occurs under distraction. This may be relevant in a real resuscitation.